Atitudinea faţă de muncă în subcultura creativă - Frunzaru, Valeriu; Ivan, Loredana (Calitatea Vieții, 2011)
This article presents the research results of a study that investigated the attitudes towards work of Romanian students. The study employs the concept of the “creative subculture” in order to indetify the specific values among students. Moreover, a paralel is made with the values of self/actualizing processes as described by Maslow (1954/2007) and with the values promoted by EU. The methodology consisted of a survey among Romanian students using a questionnaire. The results show that the attitudes towards work that can be subscribed to creative subculture are to be found among Romanian students. However, a significant proportion of female students and most male students share the attitudes and values belonging to traditional subculture. This might prove to make difficult the implementation of the European Strategy for Employment in respect to equal opportunities on the labour market.